Performance of Food Waste Feeding Pilot Plant Biodigester Operated with Identified Potential Substrate Properties - Yahaya, Siti Hajar; Mohd Said, Syafi'ah Nadiah; Zain, Mohd Azhar; Mohamad Zahari, Mohammed Shahrir; Umor, Noor Azrimi; Ismail, Shahrul (International Journal of Integrated Engineering, 2021)
Anaerobic digestion has been proven as sustainable process technology for organic waste conversion into renewable bio-energy. This study was conducted to evaluate the performance of mono-digestion process for different types of food waste substrates using pilot scale anaerobic bio-digester (1200 L) in terms of biogas production and the chemical oxygen demand (COD) removal efficiency. The biochemical methane potential (BMP) test of rice waste (R), vegetable waste (VW) and coconut meat residue (CMR) were tested at initial volatile solid (VS) loading of 0.1631, 1.1690, 1.0059 g VS/L, respectively at fixed inoculum/substrate (I/S) ratio of 0.5. Further study conducted by using rice waste (R) in pilot plant anaerobic bio-digester (1200L) for 43 days to investigate the reactor performance in term of COD removal efficiency. Interestingly, inoculum used for this study performs very well and able to digest food waste. Results demonstrate that the maximum specific biogas yield (SBY) was observed from rice waste (R) at 0.0587 L/kg VS compared to other substrates. Specific biogas yield (SBY) of rice waste (R) was 16.01% and 11.92% higher than substrate vegetable waste (VW) and coconut meat residue (CMR) respectively. High COD removal efficiency of pilot plant bio-digester (up to 93 %) using rice waste (R) as sole substrate indicates a good performance of reactor in treating food waste. Conversion of food waste to biogas in pilot plant bio-digester is highly potential as one of the sustainable waste treatment technology